Reliability of the conditioned pain modulation paradigm to assess endogenous inhibitory pain pathways - Lewis, Gwyn N (Pulsus Group Inc, 2012)
BACKGROUND: Conditioned pain modulation paradigms are often used to assess the diffuse noxious inhibitory control (DNIC) system. DNICs provide one of the main supraspinal pain inhibitory pathways and are impaired in several chronic pain populations. Only one previous study has examined the psychometric properties of the conditioned pain modulation technique and this study did not evaluate intersession reliability. OBJECTIVES: To evaluate and compare the intra- and intersession reliability of two conditioned pain modulation paradigms using different conditioning stimuli, and to determine the time course of conditioned pain inhibition following stimulus removal. METHODS: An electronic pressure transducer was used to determine the pressure-pain threshold at the knee during painful conditioning of the opposite hand using the ischemic arm test and the cold pressor test. Assessments were completed twice on one day and repeated once approximately three days later. RESULTS: The two conditioning stimuli resulted in a similar increase in the pressure-pain threshold at the knee, reflecting presumed activation of the DNIC system. Intrasession intraclass correlation coefficients for the cold pressor (0.85) and ischemic arm tests (0.75) were excellent. The intersession intraclass correlation coefficient for the cold pressor test was good (0.66) but was poor for the ischemic arm test (−0.4). Inhibition of the pressure-pain threshold remained significant at 10 min following conditioning, but returned to baseline by 15 min. CONCLUSIONS: Within-session reliability of DNIC assessment using conditioned pain modulation paradigms was excellent, but the applicability of assessing pain modulation over multiple sessions was influenced by the conditioning stimulus. The cold pressor test was the superior technique.